Water resource infrastructure implications of a green economy transition in the Western Cape Province of South Africa: A system dynamics approach - Pienaar, Aliza Pauline (Stellenbosch : Stellenbosch University, 2016)
Thesis (MEng)--Stellenbosch University, 2016.